Conformal gravity and the radial acceleration relation. Issue 1 (28th March 2019) - O'Brien, J. G.; Chiarelli, T. L.; Falcone, M. A.; AlQurashi, M. H.
Abstract : During the 2016 International Workshop on Astronomy and Relativistic Astrophysics (IWARA), the question was raised as to whether conformal gravity (CG) could explain the timely result which showed a universal nature found in the centripetal accelerations of spiral galaxies. At the time of the conference, the McGaugh result was only published for 2 weeks. Since then, the result has become known as the radial acceleration relation (RAR) and has been considered tantamount to a natural law. In this paper, we summarize how CG can explain the RAR in a manner consistent with the findings of the original authors without the need for dark matter.